PROSES PENGAMBILAN KEPUTUSAN KONSUMEN DALAM PEMBELIAN PRODUK LADA DI PROVINSI LAMPUNG - Nuni Anggraini; Clara Yolandika; Bambang Utoyo; Luluk Irawati (Jurnal Agrisep, 2022)
This research aims to analyse the stages of the consumer decision-making process for buying processed pepper products in Lampung. The research was conducted in several districts in Lampung. Primary data were obtained through direct observation and interviews using a questionnaire. The number of samples was 84 respondents. The data analysis method used in this research is qualitative analysis at the stage of the decision-making process. Analysis of the stages of the consumer purchasing decision making process is used to determine consumer behaviour in purchasing processed pepper products. The results of this study is that there are five stages in the consumer purchasing decision-making process in choosing, namely: (1) recognition of needs or problems, where most consumers choose with consideration of good quality, easy to reach and good taste; (2) information retrieval, mostly from oneself; (3) alternative evaluation, most of them buy because of quality and habits that have been done for a long time; (4) purchasing decisions, most consumers have planned to buy and buy products that look fresher; and (5) post-purchase behaviour, where most consumers feel satisfied with the product, so they make a repurchase of the product. Even if the products not available, most consumers are willing to look elsewhere.